Evaluasi Penerapan Standar Pelayanan Kefarmasian Di Puskesmas Kecamatan Peninjauan Kabupaten Ogan Komering Ulu Berdasarkan Permenkes Nomor 74 Tahun 2016 - Fransiska Angelina; Mona Rahmi Rulianti; Lilis Maryanti; Sonlimar Mangunsong (Jurnal Kesehatan Farmasi, 2022)
Background : For health effort development, the application of pharmaceutical service standards can be one of the supports to rationalize the use of drugs for patient safety. The Puskesmas in Peninjauan District still lacks human resources to carry out pharmaceutical services. Methods : This is a non-experimental research conducted observationally with a descriptive research design based on the guidelines from the Minister of Health Number 74 of 2016. The research subject were Peninjauan Primary Health Care and Lubuk Rukam Primary Health Care. Results : The result of this study indicated that the application of pharmaceutical services standards in 2 Primary Health Care in the Peninjauan Districts from the aspect management drugs and consumables reaches 97,23% from the clinical pharmacy service aspect to 50,60% from equipment and supporting facilities aspect reaches 83,33% and from the aspect of human resources reached 66,66%. Conclusion : From the result of the study, it can be concluded that the application of pharmaceutical service standards at Primary Health Care in the Peninjauan District reaches 74,45% and it’s categorized as pretty good. Keywords : Standards, Pharmaceutical Service, Primary Health Care, Peninjauan